How software robots can facilitate the procurement process? A case study of Siemens in the Czech Republic - Eva Křenková; Karolína Rieser; Alexej Sato (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to evaluate whether technological changes adopted in procurement can support the strategy of the firm and to observe the software robots' implementation phase in procurement. Research Design & Methods: In order to reach the article objective, a single case study methodology was applied. The analysis focused on the Siemens company. Findings: Digitalisation strategy in procurement can support the firm's strategy of global leadership and further growth through increased efficiency, focus on value-added activities, increased transparency in processes, easier cooperation between the involved parties, and the worldwide reach of suppliers. The potential for further use of software robots has been identified among repetitive processes with no value-added but securing the smooth and errorless flow of information and documents. For this purpose, we propose a more detailed definition of the procurement cycle. Implications & Recommendations: Three processes were selected for potential dedication to software robots which can serve as a recommendation to companies to improve the efficiency and competitiveness of their supply chains. Contribution & Value Added: To identify gaps for digitalisation in the procurement process, the “procurement cycle” was used. We found that the processes must be defined in a more detailed way in order to serve the analysis.
Keywords: F23; 033; 330; supply chain; procurement; digitalization; information technologies; industry 4.0; Czech Republic